Evaluation of the induction of immune memory following infant immunisation with serogroup C Neisseria meningitidis conjugate vaccines - exploratory analyses within a randomised controlled trial - Khatami, A; Clutterbuck, E; Thompson, A; McKenna, J; Pace, D; Birks, J; Snape, MD; Pollard, A (Public Library of Science, 2014)
AIM: We measured meningococcal serogroup C (MenC)-specific memory B-cell responses in infants by Enzyme-Linked Immunospot (ELISpot) following different MenC conjugate vaccine schedules to investigate the impact of priming on immune memory. METHODS: Infants aged 2 months were randomised to receive 1 or 2 doses of MenC-CRM197 at 3 or 3 and 4 months, 1 dose of MenC-TT at 3 months, or no primary MenC doses. All children received a Haemophilus influenzae type b (Hib)-MenC booster at 12 months. Blood was drawn at 5, 12, 12 months +6 days and 13 months of age. RESULTS: Results were available for 110, 103, 76 and 44 children from each group respectively. Following primary immunisations, and prior to the 12-month booster, there were no significant differences between 1- or 2-dose primed children in the number of MenC memory B-cells detected. One month following the booster, children primed with 1 dose MenC-TT had more memory B-cells than children primed with either 1-dose (p = 0.001) or 2-dose (p<0.0001) MenC-CRM197. There were no differences in MenC memory B-cells detected in children who received 1 or 2 doses of MenC-CRM197 in infancy and un-primed children. CONCLUSIONS: MenC-specific memory B-cell production may be more dependent on the type of primary vaccine used than the number of doses administered. Although the mechanistic differences between MenC-CRM197 and MenC-TT priming are unclear, it is possible that structural differences, including the carrier proteins, may underlie differential interactions with B- and T-cell populations, and thus different effects on various memory B-cell subsets. A MenC-TT/Hib-MenC-TT combination for priming/boosting may offer an advantage in inducing more persistent antibody. TRIAL REGISTRATION: EU Clinical Trials Register 2009-016579-31 ClinicalTrials.gov NCT01129518.